Trichoderma longibrachiatum-Associated Skin Inflammation and Atypical Hyperplasia in Mouse - Zhang, Gongjie; Li, Dongming (Frontiers in Medicine, 2022)
Background: The relationship between infection and tumor has attracted more and more attention. Trichoderma spp. are often isolated from tumors. However, the role they may play has not been unclear. We recently reported the isolation of Trichoderma longibrachiatum in the tissue of a patient with pulmonary spindle cell carcinoma that was confirmed as primary infection by application of laser capture microdissection and polymerase chain reaction In order to explore whether the strain is pathogenic and whether it can cause atypical cell proliferation and infiltration of NK cells and T cells, we designed a mouse infection experiment. Methods: Twelve ICR mice were randomly grouped into three groups. Cyclophosphamide was used to inhibit the immunity of mice. The mouse model of Trichoderma infection was successfully established by intracutaneous injection on the skin of back with suspension of strain PKUT180420015. The pathological manifestations of Trichoderma infection and the interaction between immune cells and fungi were observed by histopathology, immunohistochemistry and intensive fungal staining. The re-isolation of the fungus was observed by infected tissue culture. The inoculated sites appeared swelling 3 days after inoculation, and ulcers developed around 14 days. Skin specimens were obtained and then cultured at the times of 3, 7 and 14 days, respectively after inoculation. We chose the mouse 14 days after inoculation in group 3 whose ulcer was the most typical to analyze histological manifestations. Results: Inflammation, angioinvasion and necrosis were observed. Immunohistochemistry showed positive markers of KI67, CD3, CD56, GZMB, and PRF. Periodic acid-Schiff staining, periodic acid-silver metheramine staining Calcofluor staining showed fungal spores in the vascular lumen, vascular walls and around the blood vessels. Conclusions: Our studies have shown that Trichoderma longibrachiatum strain (PKUT180420015) isolated from the biopsy specimen in a patient with pulmonary spindle cell carcinoma could induce atypical hyplasia, with the expression of KI67, CD3, CD56, GZMB,and PRF in mice, indicating that the fungus may be involved in inducing atypical hyperplasia or tumorigenesis.